Change-of-Base Formula for Logarithms: Resulting in a quadratic equation

Examples with solutions for Change-of-Base Formula for Logarithms: Resulting in a quadratic equation

Exercise #1

2log7(x+1)log7e=ln(3x2+1) \frac{2\log_7(x+1)}{\log_7e}=\ln(3x^2+1)

x=? x=\text{?}

Video Solution

Answer

1,0 1,0

Exercise #2

log4(x2+8x+1)log48=2 \frac{\log_4(x^2+8x+1)}{\log_48}=2

x=? x=\text{?}

Video Solution

Answer

4±79 -4\pm\sqrt{79}

Exercise #3

Find X

log84x+log8(x+2)log83=3 \frac{\log_84x+\log_8(x+2)}{\log_83}=3

Video Solution

Answer

1+312 -1+\frac{\sqrt{31}}{2}

Exercise #4

Given X>1 find the domain X where it is satisfied:

log3(x2+5x+4)log3x<logx12 \frac{\log_3(x^2+5x+4)}{\log_3x}<\log_x12

Video Solution

Answer

1 < x < -2.5+\frac{\sqrt{57}}{2}

Exercise #5

1log2x6×log236=log5(x+5)log52 \frac{1}{\log_{2x}6}\times\log_236=\frac{\log_5(x+5)}{\log_52}

x=? x=\text{?}

Video Solution

Answer

1.25 1.25